HUBUNGAN KEPATUHAN PERAWATAN KAKI DENGAN KEJADIAN NEUROPATI PADA PASIEN DIABETES MELITUS DI RSUP H. ADAM MALIK MEDAN TAHUN 2019 - Murni Sari Dewi Simanullang; Ance M Siallagan; Rusnitha Br. Munthe (Elisabeth Health Jurnal, 2020)
Introduction. Diabetes mellitus (DM) is a metabolic disease characterized by increased blood glucose levels or hyperglycemia. Long-term hyperglycemia can cause various complications including neuropathy. Some measures can be taken to prevent neuropathy, such as foot care. The purpose of this study was to identify the relationship between adherence foot care with the incidence of neuropathy in patients with diabetes mellitus in H. Adam Malik General Hospital Medan in 2019.Method. This research is a descriptive correlational study using cross sectional design. The population in this study were all DM patients who came to the Polyclinic disease in H. Adam Malik General Hospital Medan. The sampling technique used was purposive sampling with a sample size of 44 respondents. Data collection was performed using a foot care compliance questionnaire and a neuropathic event observation sheet.Result. Data analysis with Chi-square test obtained p value = 0.001, which means there is a relationship between adherence of foot care with the incidence of neuropathy in DM patients at H. Adam Malik General Hospital Medan in 2019.Duscussion. DM patients can prevent neuropathy by doing regular foot care. Health workers and families can play a role in providing support to patients to improve the independence of doing foot care at home.